An analysis of urban features on energy consumption at neighborhood scale / Ali Soltani and Mehrnaz Mehraein - Soltani, Ali; Mehraein, Mehrnaz (2012)
There has been a growing interest in discovering the human effects on environment and energy consumption in recent decades. It is estimated that the energy required for transportation and housing are respectively, 20percent and 30percent of total energy consumption. Furthermore, the residential greenhouse emissions depend on urban forms and structures. This paper explores the effects of urban features on residential energy consumption. Different urban features were compared and discussed, including the urban density, typology, housing location, building area and construction materials. Two residential districts in Shiraz, south of Iran, were selected as case study areas. In order to achieve this goal, statistical analysis is utilized. Correlation analyses in linear regression were conducted to investigate the strength of each factor on energy consumption. It was found that certain urban form variables were meaningful in explaining the significant variances in energy use. The result shows how much impact each urban feature has on residential energy consumption. Density and climate changes have the most significant impacts on the energy consumption.